Analysis of the Logical Structure of Diagnosis and Treatment of Primary Glaucoma - Romaniuk, Irena U.; Wawrzyñczak, R.; Czechowicz-Janicka, Krystyna; Doroszewski, J. (Methods of Information in Medicine, 1983)
The authors analysed the diagnostic process and the therapy of primary glaucoma and set up a scheme of the different steps and essential components of the procedure. This scheme is to serve as a guide to action, in particular for the less experienced physician. It will also be of value in post-graduate training.
Keywords: Glaucoma Diagnosis; Glaucoma Treatment; Flow Diagrams for Medical Action